2008
DOI: 10.1002/jcb.21923
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of active membrane type 1 matrix metalloproteinase (MMP‐14) into extracellular space in microvesicular exosomes

Abstract: Membrane type 1 matrix metalloproteinase (MT1-MMP, MMP14) is an efficient extracellular matrix (ECM) degrading enzyme that plays important roles in tissue homeostasis and cell invasion. Like a number of type I membrane proteins, MT1-MMP can be internalized from the cell surface through early and recycling endosomes to late endosomes, and recycled to the plasma membrane. Late endosomes participate in the biogenesis of small (30-100 nm) vesicles, exosomes, which redirect plasma membrane proteins for extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
191
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(202 citation statements)
references
References 44 publications
8
191
0
Order By: Relevance
“…MMP-14 and integrin $1 have also been found in the exosomal fraction of human fibrosarcoma (HT-1080) and melanoma (G361) cells, both endowed with metastatic potential. Interestingly, transfer of these exosomes to recipient cells stimulated other MMP activities, potentially impacting a larger microenvironment [59]. More recently, Tauro et al demonstrated, in the H-ras induced EMT model of MDCK cells, a similar increase in the presence of MMP-14, integrin $1 and integrin "3 [11].…”
Section: Discussionmentioning
confidence: 98%
“…MMP-14 and integrin $1 have also been found in the exosomal fraction of human fibrosarcoma (HT-1080) and melanoma (G361) cells, both endowed with metastatic potential. Interestingly, transfer of these exosomes to recipient cells stimulated other MMP activities, potentially impacting a larger microenvironment [59]. More recently, Tauro et al demonstrated, in the H-ras induced EMT model of MDCK cells, a similar increase in the presence of MMP-14, integrin $1 and integrin "3 [11].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the adverse tumor microenvironment somehow triggers tumor cells to release microvesicles, which in turn facilitates angiogenesis by bringing nutrients and oxygen to the rescue of cancer cells. ECM degradation upon rupture of released microvesicles (Angelucci et al, 2000;Ginestra et al, 1998;BajKrzyworzeka et al, 2006;Sidhu et al, 2004 ECM modification and MMP activation (Hakulinen et al, 2008;Giusti et al, 2008;Taraboletti et al, 2006;Dolo et al, 1998 …”
Section: Microvesicles and Tumor Angiogenesismentioning
confidence: 99%
“…As indicated above, microvesicles that are shed by tumor cells are loaded with proteases and provide an additional means of matrix degradation, creating a path of least resistance for invading tumor cells. Accordingly, studies report the presence of MMP2, MMP9, MT1-MMP and their zymogens urokinase-type plasminogen activator (uPA) and EMMPRIN, within tumor-derived microvesicles (Angelucci et al, 2000;Ginestra et al, 1998;Baj-Krzyworzeka et al, 2006;Hakulinen et al, 2008). MMPs degrade basement collagens, whereas uPA catalyzes the conversion of plasminogen into plasmin, a serine protease that facilitates the conversion of MMP zymogens into their active forms as well as the degradation of matrix components such as fibrin (Angelucci et al, 2000).…”
Section: Impact On Tumor Invasion and Metastasismentioning
confidence: 99%
“…Recently, it was discovered that MMP-14 can be secreted in exosomes [16], however MMP-14 often works while at the cell membrane and in close proximity to ECM attachment. For instance, MMP-14 localizes to perinuclear regions that are in close contact with ECM that form small pores, hindering the advance of the nucleus [17,18].…”
Section: Introductionmentioning
confidence: 99%